A percepção dos cidadãos de Uberlândia sobre espaços livres públicos - Segismundo, Mateus Duarte (2024)
Public open spaces are important areas for the development of the urban context since these spaces can generate quality of life for the population. However, to achieve this goal, they must be well planned and structured so that people can have positive and pleasant experiences when visiting these places In this sense, in order to understand whether the residents of Uberlândia are really having this experience, this study had as its main objective to investigate whether the elements that make up the municipal parks of Uberlândia, such as infrastructure, location, activities and uses, allow the diagnosis of the capacity to promote quality of life associated with the functions of this category of Public Free Spaces. To achieve this goal, it was necessary to carry out several methodological procedures that were structured into a few stages: the development and application of an online questionnaire, the adapted formulation of a Likert scale from 1 to 5, the simple and weighted arithmetic averages, the categorization of emotional data, and finally, the creation of emotional maps. Thus, through an overview, the results indicated that the municipal parks are able to generate positive affective bonds in the population, with Sabiá Park having the best perceptions, while the Uberabinha River Linear Park had the lowest. Despite these positive responses, the results indicate that the elements present in the park (infrastructure, localization, activities and uses) could be improved to achieve even higher rates. In addition, it was found that the city's residents see these spaces as having the main leisure function, with only the exception of the Victório Siquierolli Municipal Park, which was perceived as having the primary ecological function. This shows that, for the most part, the residents of Uberlândia associate these spaces as places for recreational activities, aimed at rest and entertainment. In this sense, it is understood that the emotional results obtained in this research can contribute to informing managers and the population.